Tinjauan Teologis Terhadap Fenomena LGBT Bagi Gereja dan Masyarakat Masa Kini - Putra, Adi; Zebua, Marta Novianti; Nome, Nehemia; Keluanan, Yane Henderina (Jurnal Kala Nea, 2023)
This research specifically examines the phenomenon of LGBT in society. The goal is to produce a perspective and an effective way that the Church and society should do to serve and heal LGBT sufferers. This research uses qualitative methods, especially literature review to describe, analyze to produce new propositions on this topic. Through this research, several conclusions were obtained. First, LGBT is a sin and a mistake that arises as a result of sin, so it needs to be addressed with great care and wisdom so that you don't react wrongly. Second, the role of the Church is so significant in serving every person with LGBT. The church must not excommunicate or reject them, but it must not ostensibly justify their every wrong action. On the other hand, the church must firmly say that LGBT is a mistake and a sin that violates God's glory, while the church carries out pastoral actions and services to heal and restore them. Third, apart from the church, the role of the general public is also significant. Because society must help every person with LGBT to realize and want to improve their life that has deviated from God's will.